Analysis of the psychometric properties of a questionnaire to measure the intensity of discomfort due to lying in the relationship of young couples using the Rasch model - Yáñez Canal, Gabriel (2020)
This article presents an analysis using the Rasch model of the psychometric properties of a questionnaire elaborated to measure the level of intensity of the discomfort that young heterosexuals feel due to a partner’s lie. The test consists of 15 items and was administered to 503 male and female students in university undergraduate courses between the ages of 16 and 22, who had experience in relationships. The results show the good fit of the data to the model, guaranteeing the validity of the questionnaire. Although the initial test is well-constructed and compatible with most of the levels of the students surveyed, new items could be designed to extend the range of measures of discomfort and thereby increase theinstrument’s validity.